Anti-hyperglycemic fraction from Alternanthera sessilis L. leaves gets elucidated following bioassay-guided isolation and mass spectrometry (Brazilian Journal of Pharmaceutical Sciences, 2023)
The anecdotal use of Alternanthera sessilis L. as a relief for diabetes has been known in the Philippines for generations, and antidiabetic activity of similar varieties in other countries is likewise documented. However, the compounds responsible for this activity remain unclear. This study aims to isolate the anti-hyperglycemic fraction of local A. sessilis leaves and identify the compounds in this fraction. Methanol extract of A. sessilis leaves and its hexane, ethyl acetate (ASE), and water fractions were administered to alloxan-induced diabetic mice. ASE (250mg/kg) had the highest anti-hyperglycemic activity at 6-h post-treatment (25.81%±12.72%), with almost similar blood glucose reduction rate as metformin (30.13±3.75%, p=0.767). Repeated fractionation employing chromatographic separation techniques followed by in vivo anti-hyperglycemic assay yielded partially purified subfractions. A. sessilis ethyl acetate subfraction 4-2 (100mg/kg) displayed remarkable suppression of blood glucose rise in diabetic mice at 6-h post-treatment (26.45±3.75%, p<0.0001), with comparable activity with metformin (100mg/kg, 27.87±5.65%, p=0.652). Liquid chromatography/mass spectrometry showed eight distinct peaks, with four peaks annotated via the Traditional Chinese Medicine library and custom library for A. sessilis. Among these, luteolin, apigenin, ononin, and sophorabioside were identified as putative compounds responsible for the anti-hyperglycemic activity. This result provided basis for the reported anecdotal claims and potential utility of the local variety of A. sessilis leaves as sources of anti-hyperglycemic agents.